Implementation of Interactive Multimedia to Improve Science Literacy of Elementary School Students: Systematic Literature Review - Hodaifah, Hodaifah; Widodo, Wahono; Prahani, Binar Kurnia (Papanda Publisher, 2025)
The low level of scientific literacy among elementary school students is a serious challenge in the world of education, especially in facing the demands of the 21st century which emphasizes critical thinking skills, problem solving, and understanding scientific concepts. One of the causes is the lack of interesting learning media that can accommodate students' learning needs as a whole. Therefore, innovation is needed in the form of interactive learning multimedia that can present material in an attractive visual way and actively involve students. This study aims to implement and examine the effectiveness of using interactive learning multimedia in improving elementary school students' scientific literacy. This study uses the Systematic Literature Review (SLR) method to analyze and synthesize various relevant studies on the implementation of interactive learning multimedia in the context of improving scientific literacy. Data were collected from various reputable national and international journals in the period 2017 to 2023, using databases such as Google Scholar, DOAJ, and GARUDA. The selection process was carried out with strict inclusion and exclusion criteria to obtain relevant and quality articles. A total of 10 articles were selected for analysis. The results of the study showed that most studies concluded that interactive multimedia has a positive influence on improving students' scientific literacy skills. This media has been proven to improve conceptual understanding, critical thinking skills, and increase students' interest and motivation to learn. In addition, the use of visual elements, animation, and simulation in multimedia can bridge students' difficulties in understanding abstract concepts in science. Thus, it can be concluded that interactive learning multimedia tends to be effective and relevant in improving elementary school students' scientific literacy. However, limitations such as small sample sizes or context-specific findings in some studies should be considered. These findings provide implications for teachers, media developers, and policy makers to integrate multimedia technology more optimally in science learning.